Essential content of fundamental rights: theoretical foundation and reasonableness criteria in the Ecuadorian legal system - López Ruiz, Iliana (2023)
The present study assesses the different theories that address the essential content of fundamental rights. It is analyzed from a constitutional perspective, essentially seen as a guarantee that operates before the legislator. The research carries out an analysis of comparative law examining jurisprudence from countries such as Spain, Peru, Colombia, to finally concatenate the development of these theories in Ecuador. The fundamental objective is focused on critically addressing the Ecuadorian jurisprudential development in terms of determining the essential content of rights, and proposes the application of new reasonableness criteria to establish its content and scope. To achieve this objective, the qualitative method of scientific research is implemented, essentially in relation to the collection of information on aspects related to theoretical approaches that revolve around the determination of the essential content of fundamental rights. Finally, with this study it is concluded that the main difficulty that arises in the Ecuadorian constitutional legal system is the fact that a hierarchy of rights is not instituted; that is to say, it is urgent for Ecuador to develop clear standards from the normative point of view to determine the essential content of rights; taking into account fundamental elements such as the legal nature, the protected asset, its purpose and its functional exercise, to this is added the proposal of the application of reasonableness criteria to optimize the assessment of the essential content of the rights, especially when these are in contradiction.